Hybrid PV and solar-thermal systems for domestic heat and power provision in the UK: Techno-economic considerations - Markides,CN; Herrando,M (Applied Energy, 2015)
A techno-economic analysis is undertaken to assess hybrid PV/solar-thermal (PVT) systems for distributedelectricity and hot-water provision in a typical house in London, UK. In earlier work (Herrando et al., 2014), asystem model based on a PVT collector with water as the cooling medium (PVT/w) was used to estimateaverage year-long system performance. The results showed that for low solar irradiance levels and lowambient temperatures, such as those associated with the UK climate, a higher coverage of total householdenergy demands and higher CO2 emission savings can be achieved by the complete coverage of the solar collectorwith PV and a relatively low collector cooling flow-rate. Such a PVT/w system demonstrated an annualelectricity generation of 2.3 MW h, or a 51% coverage of the household’s electrical demand (compared to anequivalent PV-only value of 49%), plus a significant annual water heating potential of to 1.0 MW h, or a 36%coverage of the hot-water demand. In addition, this system allowed for a reduction in CO2 emissionsamounting to 16.0 tonnes over a life-time of 20 years due to the reduction in electrical power drawn fromthe grid and gas taken from the mains for water heating, and a 14-tonne corresponding displacement of primaryfossil-fuel consumption. Both the emissions and fossil-fuel consumption reductions are significantlylarger (by 36% and 18%, respectively) than those achieved by an equivalent PV-only system with the samepeak rating/installed capacity. The present paper proceeds further, by considering the economic aspects ofPVT technology, based on which invaluable policy-related conclusions can be drawn concerning the incentivesthat would need to be in place to accelerate the widespread uptake of such systems. It is found that,with an electricity-only Feed-In Tariff (FIT) support rate at 43.3 p/kW h over 20 years, the system cost estimatesof optimised PVT/w systems have an 11.2-year discounted payback period (PV-only: 6.8 years). Therole and i